Nanoparticle shapes boundary layer flow in nanofluid and their effects on heat transfer - Al-Nasrawi, Jaafar Abdul Abbas Abbood (2022)
This thesis investigated two-dimensional, viscous and incompressible boundary layer flow models subject to different stream conditions. The nanoparticles such as copper or a single-walled carbon nanotube are suspended in a base fluid-water, in order to investigate heat transfer characteristics. The thermophysical properties such as empirical nanoparticle shapes and nanoparticle volume fraction are utilized to examine the nanofluid according to the Tiwari-Das approach in four problems. The governing partial differential equations were transferred to the ODEs using similarity transformations, solved by the Runge-Kutta-Fehlberg method and the shooting technique programmed in Maple 18. Firstly thermal radiation and viscous dissipation are modeled on the mixed convection heat transfer over a nonlinear moving sheet. The stagnation point flow is considered in the presence of a magnetic field with a permeable surface. It is found that the temperature for nanoparticle sphere shapes to be the lowest compared to a cylinder and laminar shapes due to differences in internal energy or kinetic energy and nanoparticle movement on the surface. Secondly is the unsteady Carreau nanofluid model with the squeezed flow between two parallel flat plates, including the sensor surfaces. It is found that the temperature profiles for non-permeable surface is lower than permeable surface. Further, the temperature for nanoparticle lamina shape is the lowest compared to sphere and cylinder shapes. Thirdly is the Carreau nanofluid model on the nonlinear moving surface with variable wall thickness. The electrical field impact with the magnetohydrodynamic flow is scrutinized. It is found that an increase in volume fraction led to an increased heat transfer rate in shear-thinning and shear-thickening. An increase in nanoparticle volume fraction led to a slight increment of mass transfer. Finally, the Cattaneo-Christov heat flux model on Maxwell nanofluid with suction/injection over a stretching sheet was examined. An increase in nanoparticle volume fraction leads to increased heat transfer rate and a slight decrease in mass transfer rate. Various dynamical parameters and physical properties were presented in graphical of velocity, temperature, and concentration with heat and mass transfer analysis.